Hubungan Status Gizi dan Tingkat Pendapatan dengan Kejadian Tuberkulosis Paru di Wilayah Kerja Puskesmas Benu-Benua - Erpiono, Erpiono; Demmalewa, Jenny Qlifianti; Dhesa, Desidarius Bela; Abadi, Ellyani; Ihsan M, Habib (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2023)
Tuberculosis (TB) is a direct infectious disease caused by Mycobacterium tuberculosis, Mycobacterium bovis or Mycobacterium africanus. TB is one of the top 10 causes of death worldwide caused by the bacillus Mycobacterium tuberculosis. Most TB germs attack the lungs, but can also attack other organs. The purpose of this study was to determine the relationship between nutritional status, income and pulmonary tuberculosis in the working area of ​​Benu-Benua Health Center. This type of research is observational with a cross sectional study design, where the research subjects are observed at the same time. The population of this study were patients who visited the Continental Health Center and were recorded in the medical record in the pulmonary TB disease eradication room. 0.837. There is a relationship between nutritional status and the incidence of pulmonary TB in the working area of ​​the Benu-Benua Health Center marked by the value of value = 0.015. Suggestion: For further researchers, it is recommended to add other factors such as household contact and house ventilation. For puskesmas officers to be able to provide counseling about pulmonary TB to the community. For patients with pulmonary TB in order to maintain their nutritional status and pay attention to the cleanliness of the food consumed.